2023
DOI: 10.1007/s12178-023-09828-0
|View full text |Cite
|
Sign up to set email alerts
|

Stronger Athlete Identity Is a Risk Factor for More Severe Depressive Symptoms After Musculoskeletal Injury in Pediatric Athletes: a Systematic Review

Abstract: Purpose of Review Treatment for musculoskeletal sports injuries often neglects the psychological components of health and recovery. Pediatric patients require particular consideration of their psychosocial and cognitive development. This systematic review investigates the effects of musculoskeletal injury on mental health in pediatric athletes. Recent Findings Athlete identity may increase in adolescence and is associated with worse mental health post-inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In a scoping review of 22 studies and 1852 athletes, Renton et al [35] reported that athletic identity was most frequently associated with psychosocial, behavioural and injury-specific outcomes. In a systematic literature review, Park et al [32] found that in paediatric athletes, musculoskeletal injury was associated with worse mental health, and stronger athlete identity was a depression risk factor. In a study of 269 adolescent tennis players, Johansson et al [16] suggested that higher athletic identity was associated with a greater likelihood for an athlete to attempt to 'play through pain'.…”
Section: Discussionmentioning
confidence: 99%
“…In a scoping review of 22 studies and 1852 athletes, Renton et al [35] reported that athletic identity was most frequently associated with psychosocial, behavioural and injury-specific outcomes. In a systematic literature review, Park et al [32] found that in paediatric athletes, musculoskeletal injury was associated with worse mental health, and stronger athlete identity was a depression risk factor. In a study of 269 adolescent tennis players, Johansson et al [16] suggested that higher athletic identity was associated with a greater likelihood for an athlete to attempt to 'play through pain'.…”
Section: Discussionmentioning
confidence: 99%
“…The strength with which an athlete identifies as an athlete is called athlete identity [ 29 ]. Strong athletic identity is considered a risk factor for mental health problems following injury [ 30 ]. The threat of losing that identity due to injury and psychological distress related to injury is associated with retirement from sport and may explain why the correlation between perceived stress and injury was stronger among male than among female players.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to high athletic identity, the concept that athletes define themselves based on their sport or activity, which then serves as a basis of their sense of self-worth. 29 A study by Furie et al. 30 found that injured athletes showed greater rates of anxiety and depression compared with the general population and those who had to involuntarily retire from their sport had increased psychological distress.…”
Section: Discussionmentioning
confidence: 99%